BIOECOLOGICAL PROPERTIES OF WATER PLANT OF AZOLLA (AZOLLA CAROLINIANA WILLD) - Qodirova Soxiba Ravshanbek qizi,; Xudayberganov Norbek Atabaevich,; Abdullayeva Madina Yusupboy qizi,; Abdusharipova Guljonoy Qobul qizi, (TADQIQOTLAR.UZ, 2024)
Annotation: Botanical description of the aquatic plant Azolla (Azolla caroliniana). Azolla (Azolla caroliniana) is a cycle of growth, development and reproduction methods as well as seasonal development. Distribution on Earth. Azolla's (Carolina) monetology and its importance in agriculture and public administration.